The haunted mansion [videorecording (DVD)] - Gunn, Andrew, 1969-; Hahn, Don; Berenbaum, David; Minkoff, Rob; Murphy, Eddie, 1961-; Stamp, Terence; Parker, Nathaniel, 1962-; Thomason, Marsha, 1976-; Tilly, Jennifer, 1958-; Shawn, Wallace; Spybey, Dina, 1966-; Jefferies, Marc John; et al. (Disney DVD., 2004)
Jim Evers is a real estate agent whose latest project is to find a buyer for a huge but dilapidated old house in New Orleans. However, when Evers and his family visits the property before their family vacation, he discovers it's already inhabited by 999 ghosts, none of whom are interested in sharing the space. As the spirits make their displeasure known, Evers and his family, with the help of an eccentric medium named Madame Leota, try to get the ghosts to leave.